Kedudukan Ruang Bioskop Sebagai Media Apresiasi Film - Rembulan, Dara Bunga (Capture : Jurnal Seni Media Rekam, 2011)
Movie is one of mediums for delivering messages communicatively and easily acceptablefor the society. The creativity of filmmaker has caused a rapid increase in the amount ofmovies, and further it indirectly lead to the increase in necessity of space for appreciationactivities. It can be concluded that movie theatre is one of the appreciation media thatis highly favored by the movie-favored-society. There are two types of movie theatres,mainstream and non-mainstream movie theatre. A mainstream movie theatre is the 21network movie theatre, while the non-mainstream movie theatre consists of filmfestivals, discussions, and workshops. A movie theatre is an alternative medium formovie appreciation. By the movie theatre which is able to attract audiences, it can befigured out how far the movie theatre is able to become appreciation medium for thesociety. As we know that there are lots of other appreciation mediums such as VCD,DVD and internet that are growing in the society, so the functional approach can helpto find the answers in the growth of a movie theatre as movie appreciation medium.